O estudo da relação ternária para o ensino do Campo Conceitual Multiplicativo - Souza Couto, Maria Elizabete (2021)
This article aims to analyze and describe the formative process of teachers in the early years who teach the concepts of Multiplicative Comparison. A qualitative research carried out during a training process with teachers who worked in the early years of elementary school. The training was organized in face-to-face meetings, virtual meetings and pedagogical practice activities, having as content the Multiplicative Conceptual Field (CCM) studied by Gérard Vergnaud. A result, the training process provided evidence of expanding mathematical knowledge in the face of the problem situations of the CCM, strengthening: the practice of teachers; elaboration of problem situations with different complexities (multiplication and division); the work mediated in the classroom, observing the schemes used by the students and the concepts that still needed interference to effect learning, demonstrated possibilities for new strategies for the teacher to understand the construction of students' mathematical knowledge.